Investigating the Impact of Growth Variables an ARDL Bound Testing Approach - Ibrahim, Ladan; M.U. , Adehi; M.O, Adenomon, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study examines the impact of inflation, interest rates, and exchange rates on the Nigerian economy using time series data from the CBN spanning from 1986 to 2022. With two main objectives, it investigates their effects and estimates the short-term impact on GDP. Utilizing methods like Augmented Dickey-Fuller unit root test, Autoregressive Distributed Lag (ARDL) Bound Test, and Granger causality test, the study establishes an ARDL short-run model to measure the influence of GDP, inflation, interest rates, and exchange rates on economic growth. Diagnostic tests, including the Fisher test, validate the model, explaining 98.5% of GDP variation. Stability in model parameters and error term constancy is confirmed by CUSUM tests, affirming the model’s robustness. Granger causality tests indicate that GDP does not precede inflation, interest rates, or exchange rates. The study underscores the importance of stabilizing exchange rates for consistent short-term economic performance in Nigeria, urging policymakers to prioritize monitoring and stabilization measures.